Perencanaan Taman Islami Berbasis EDEN (Educational-Dynamical-Ecological-Natural) di Pondok Pesantren Tahfidz Qur’an Dewan Dakwah Lampung - Nurrahmah, Rizky Aulia; Franjaya, Eduwin Eko (Jurnal Arsitektur Lansekap; Vol.8, No.2, Oktober 2022, 2022)
Islamic Garden Planning Based on EDEN (Educational-Dynamical-Ecological-Natural) in Pondok Pesantren Tahfidz Qur’an Dewan Dakwah Lampung. Pondok Pesantren Tahfidz Qu’an Dewan Dakwah Lampung is one of the centers of religious education in Kecamatan Kemiling, Bandar Lampung. As an educational area in a strategic region, PPTQ Dewan Dakwah Lampung has the potential to make Bandar Lampung even more advanced. Reciprocity between the government and residents is needed in structuring the PPTQ Dewan Dakwah Lampung related to optimization the land use. The research aims to plan a landscape that can create a quality place to support activities and fulfill user needs. This research used a survey and descriptive qualitative methods. The data were collected through field observation, interview, and literature study, for further were analyzed refers to the complete design process. The research results direct the landscape to an EDEN-based concept (Educational-Dynamical-Ecological-Natural) included in Islamic Placemaking in EDEN (I-PLAN). The application of the elements presented in the site plan or 3D models is adjusted to the concept of an Islamic Garden. By applying I-PLAN can be a safe and comfortable means of education, contemplation, recreation, and behavior guide for users.